Applying game-based learning to a primary school class in computer science terminology learning - Kaldarova, Bolganay; Omarov, Bakhytzhan; Zhaidakbayeva, Lyazzat; Tursynbayev, Abay; Beissenova, Gulbakhram; Kurmanbayev, Bolat; Anarbayev, Almas (Frontiers in Education, 2023)
Game-based learning is an innovative technique that utilizes the educational potential of videogames in general, and serious games in particular, to enhance training processes and make it simpler for users to attain motivated learning. In this study, we propose game based learning for primary school students in computer science terminology learning. Primary school students often engage in game-based learning. Academic accomplishment motivation consequences have been researched extensively. The purpose of this research was to see how successful Game-Based Learnings are in motivating primary school kids to attain academic success. Fifty primary school students in two focus groups participated in the experiment during ten weeks to test the involvement of game based learning to pupils. There are two kind of measurements were applied in identifying benefits of game based learning. First, one is the questionnaire that students answered to questions in three categories as Impression, Usability, and User Interface. Second part of measurement is downloading and uploading of hometasks, and their academic performance. Approximately 90% of the students found the game based learning to be beneficial in their studies and remembering computer science terminologies. The children were satisfied with its functionality and ease of use. The results can be useful for educators, instructional and game designers, and researchers from implementation, design and research perspectives.